The dissociation of ammonium salts and their effect on the physiology and biochemistry of L-lysine synthesis by Corynebacterium glutamicum FP6 - Kenyon, Colin Peter (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1994)
The availability and assimilation of NHâ‚„â º plays an integral role in the growth of microorganisms and the production of amino acids by these organisms. This study investigated the dissociation of NHâ‚„â ºin aqueous solution, its availability and effect on the enzymes of NHâ‚„â º assimilation and its influence on lysine production by Corynebacterium glutamicum.In aqueous solution the extent of dissociation of NHâ‚„C1, {NHâ‚„)â‚‚S0â‚„ and (NHâ‚„)â‚‚HP0â‚„ increases with decreasing concentration. A model is proposed for the dissociation of these molecules. It is believed that at very low concentrations, dissociation to NHâ‚ƒ plus the respective counter-ions occurs. At these low concentrations the NHâ‚ƒ acts as the substrate for glutamine synthetase. At the higher concentrations dissociation is to NHâ‚„â º which is the substrate for glutamate dehydrogenase. At these higher concentrations the enzyme activities obtained for glutamate dehydrogenase, at equivalent concentrations of the above ammonium salts, were different when based on the total concentration of NHâ‚„â º, and similar when based on the concentration of free NHâ‚„â º. L-Iysine occurs in the +1 ionic form, at pH 7,2. The lysine which is produced during fermentation associates with the anionic counter-ion of the ammonium salt used. The concentration of the free NHâ‚„â º in the media appears to affect both the rate of lysine synthesis as well as the yield. The lysine fermentation occurs in two stages; a growth (or replicative) phase, during which very little lysine is produced, and a lysine syn
Keywords: Ammonium salts; Lysine -- Synthesis; Corynebacterium; Dissociation -- Research